“FRAMING MEDIA DALAM BERITA MAJUNYA SETYA NOVANTO KEMBALI MENJADI KETUA DPR” - Ferry Eko Adi Prasetyo; Buddy Riyanto, Maya Sekarwangi (Solidaritas, 2017)
“FRAMING MEDIA DALAM BERITA MAJUNYA SETYA NOVANTO KEMBALI MENJADI KETUA DPR” OlehFerry Eko Adi PrasetyoBuddy RiyantoMaya Sekarwangi ABSTRACTThe advantages of online media is its speed on delivering events or events. Preaching Setya Novanto back to the Speaker of the house in the media online Viva.co.id and Metrotvnews.com. This research to know how construct the facts and convei an event to the public. Using framing analysis, research results show that both online media have different wais of constructing reality.Keyword : Framing, online Media, Media Reality.